THE USE OF INTERACTIVE PEDAGOGICAL TECHNOLOGIES IN THE FORMATION OF LABOR EDUCATION - Yusupova Roza Amanbay qizi (Scholar Express Journals, 2025)
The use of interactive pedagogical technologies in labor education plays a crucial role in shaping students' professional skills, work ethic, and responsibility. This study examines the effectiveness of various interactive teaching methods, such as project-based learning, role-playing, case studies, and digital tools, in enhancing students' engagement and practical competencies. By integrating these technologies, educators can create a more dynamic learning environment that fosters creativity, problem-solving abilities, and teamwork. The findings highlight the importance of interactive approaches in preparing students for real-world labor challenges and improving their overall educational outcomes
Keywords: Interactive pedagogical technologies; labor education; project-based learning